Kinetika Reaksi Sintesis Glukosa dari Limbah Padat Yeast (Yeast Mud) Menggunakan Proses Hidrolisis Asam - Dimas Nur Arifianto; Rasendriya; Retno Dewati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Glucose is usually used in the production of liquid sugar, syrup and as an alternative energy source such as bioethanol. An alternative material for the production of glucose is to use waste residues that can still be used, such as solid yeast waste (yeast sludge) from PT. Energi Agro Nusantara, which has a relatively high carbohydrate content of 31.55%. This research was conducted in 3 stages. The first stage is the preparation of raw materials, followed by the production of liquid glucose by acid hydrolysis method and the determination of reaction order and reaction rate constant. The hydrolysis was carried out at a constant temperature of 900C, stirring speed of 200 rpm, material ratio of 1:10, HCl concentration: 2.5N; 3N; 3.5N; 4N; 4.5N, and hydrolysis time: 60 min; 90 min; 120 min; 150 min; 180 min. The results of the study showed that the glucose synthesis reaction from yeast sludge solid waste followed a pseudo first order reaction, and the glucose content of the hydrolysis results was influenced by the concentration of HCl catalyst and the duration of hydrolysis, which had a directly proportional effect. The highest glucose content obtained was 26% and the reaction rate constant (k) value was 0.0046 at a concentration of 4.5 N HCl with a hydrolysis time of 180 minutes.